(untitled) (Research, Society and Development, 2020)
Coronavirus is one of the main pathogens that targets the human respiratory system. In Brazil, the first confirmed case of a COVID-19 patient was registered in the state of São Paulo on February 26, 2020. On April 30, 2020, Brazil has more confirmed cases (85,380 confirmed cases and 5,901 deaths ) more than China (83,944 cases and 4,637 dead) (WHO, 2020). In view of this situation, this scientific article has the general objective of investigating the epidemiological profile of COVID-19 in Brazil. To this end, a bibliographic and documentary study on epidemiology was carried out, taking into account statistical data about the reality of the pandemic in the country. The units of analysis were Brazil, its macro-regions and UFs. Brazil has 5,570 municipalities divided into 27 FUs, which are grouped into five geographic macro-regions (Midwest, Northeast, North, Southeast and South), which have very different sociodemographic and health characteristics. For the epidemiological situation, the period November and December 2020 was considered. Data on cases and deaths confirmed by the disease, by place of residence and aggregated by country, geographic macro-region and UFs in Brazil, made available by the COVID-19 Panel were used. of the Ministry of Health in a public, grouped and non-nominal way.